In Tandem : The Painter-Sculptor in the Twentieth Century. - Cooke, Lynne (London : Whitechapel Art Gallery, 1986)
Artschwager, Richard ; Bartlett, Jennifer ; Baselitz, Georg ; Boccioni, Umberto ; Clemente, Francesco ; Degas, Edgar ; Dubuffet, Jean ; Fontana, Lucio ; Giacometti, Alberto ; Johns, Jasper ; Katz, Alex ; Kelly, Ellsworth ; Kirchner, Ernst Ludwig ; de Kooning, Willem ; Lichtenstein, Roy ; Matisse, Henri ; Miró, Joan ; Newman, Barnett ; Picasso, Pablo ; Schnabel, Julian ; Twombly, Cy
In Tandem : The Painter-Sculptor in the Twentieth Century, Whitechapel Art Gallery, London, 27 March - 25 May 1986
boek